PENGEMBANGAN MODUL BERBASIS STRATEGI PQ4R UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN SELF EFFICACY SISWA - Fertilia Ikashaum; Sri Hastuti Noer (Fakultas Tarbiyah dan Ilmu Keguran IAIN Metro, 2020)
Mathematical modules are important to study related to the development needs of students' critical thinking processes. Students' confidence when solving critical thinking questions contained in the module independently also becomes important to note. The purpose of this research and development is to develop mathematical modules and their effectiveness on the ability to think critically mathematically and self-efficacy of students to improve. Limited testing is done after validation by experts and initial trials on small groups of students. The effectiveness test in one class of students shows modules that already have a good category on the content standard, media, and language feasibility can make students meet the minimum completeness criteria. While students' self efficacy tends not to show significant changes.